2021
DOI: 10.1002/jbt.22697
|View full text |Cite
|
Sign up to set email alerts
|

Boldine treatment protects acetaminophen‐induced liver inflammation and acute hepatic necrosis in mice

Abstract: Drug‐induced liver injury (DILI) is a frequent cause responsible for acute liver failure (ALF). Acetaminophen (APAP) is a known hepatotoxin predictably causing intrinsic DILI. At high doses, APAP causes acute liver necrosis and responsible for ALF and liver transplant cases in 50% and 20% of patients, respectively, in the United States alone. Oxidative stress and glutathione depletion are implicated in APAP‐induced liver necrosis. Boldine, a plant‐derived compound is shown to have promising antioxidant potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
(68 reference statements)
2
14
0
Order By: Relevance
“…Previous studies have shown that administration of more than 300 mg/kg/day of SV can cause hepatotoxic markers enzymes (AST, ALT, and ALP) elevation and micro‐anatomical changes in liver tissue of rats 10,35 . The AST, ALT, and ALP enzymes are confined to hepatocytes, whenever there is a hepatocellular degeneration caused by certain drug metabolites, liver cells liberate these enzymes into the systemic circulation 36,37 . Clinically, AST, ALT, and ALP elevations have been reported as one of the common phenomena of DILI 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that administration of more than 300 mg/kg/day of SV can cause hepatotoxic markers enzymes (AST, ALT, and ALP) elevation and micro‐anatomical changes in liver tissue of rats 10,35 . The AST, ALT, and ALP enzymes are confined to hepatocytes, whenever there is a hepatocellular degeneration caused by certain drug metabolites, liver cells liberate these enzymes into the systemic circulation 36,37 . Clinically, AST, ALT, and ALP elevations have been reported as one of the common phenomena of DILI 38 .…”
Section: Discussionmentioning
confidence: 99%
“…10,35 The AST, ALT, and ALP enzymes are confined to hepatocytes, whenever there is a hepatocellular degeneration caused by certain drug metabolites, liver cells liberate these enzymes into the systemic circulation. 36,37 Clinically, AST, ALT, and ALP elevations have been reported as one of the common phenomena of DILI. 38 In clinical subjects, SV has been known to cause hepatocellular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no association between the individual effect of this drug and the risk of abnormal elevation of ALT in the logistic LASSO regression model. Acetaminophen is a known hepatotoxin causing intrinsic DILI, which is related to increasing dose ( Ezhilarasan and Raghunandhakumar, 2021 ). It is proposed that the safe dose of acetaminophen to avoid liver injury is ≤ 4 g/day for an adult ( Jaeschke, 2015 ), and the maximum approved dose of acetaminophen is 4 g/day in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Several intervention studies confirmed that TNF expression alters the severity of AILI [ 89 , 166 , 191 , 226 , 227 ]. Combination therapy of boldine and NAC significantly reduces the expression of inflammatory markers, including TNF-α, IL-1β, and IL-6 [ 228 ]. Poria cocos polysaccharides pretreatment attenuates AILI by decreasing the expression of TNF-β and tumor necrosis factor receptor (TNFsR)-I [ 229 ].…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 99%